Mapping Forest Landscape Patterns 2017
DOI: 10.1007/978-1-4939-7331-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automated Forest Mapping

Abstract: The need for up-to-date and accurate information on forest resources has rapidly increased in recent years. Forest mapping is an important source of information for the assessment of woodland resources and a key issue for any National Forest Inventory (NFI). Nowadays, new perspectives for automated forest mapping are emerging through the latest developments in remote sensing data and techniques.In this chapter, an overview of current remote sensing data and techniques for mapping woodland and forests, the chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Within the last decades, various remote-sensing-based methods have been developed and studied. Remote sensing has the potential to provide consistent, reproducible and up-to-date information on various forest parameters in order to make inventories more efficient [6]. Previous studies mostly applied a specific remote sensing system to a single area and demonstrated how remote sensing can be used for quick assessment of forests at large spatial scales (see, e.g., [7][8][9][10][11][12][13][14][15][16]).…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decades, various remote-sensing-based methods have been developed and studied. Remote sensing has the potential to provide consistent, reproducible and up-to-date information on various forest parameters in order to make inventories more efficient [6]. Previous studies mostly applied a specific remote sensing system to a single area and demonstrated how remote sensing can be used for quick assessment of forests at large spatial scales (see, e.g., [7][8][9][10][11][12][13][14][15][16]).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of a logarithmic variable radius in Equations (2) and 3is based on the observed relationship between upper crown radius and tree height in the region of interest. However, this relationship may vary significantly between forest types [30] and other variable radius functions such as those proposed in [31][32][33] may be used in place of Equations (2) and 3.…”
Section: Step 1-initial Segmentationmentioning
confidence: 99%
“…Airborne Laser Scanning (ALS) is an effective technology to support forest survey, research and management [1][2][3]. ALS can provide valuable data on forest structure and composition, in the form of dense 3D point clouds which can be further processed to create a range of useful products (such as topographical relief, canopy height, canopy layering, timber volume, canopy fuel characteristics, stand/edge delineation and deciduous/coniferous proportion).…”
Section: Introductionmentioning
confidence: 99%
“…For the foreseeable future, autonomous forest machines (AFMs) will play a central role in harvesting, tending and forest management because lots of artificial and natural forests are facing with poor forest quality on a large-scale [ 1 ]. Currently, the proportion of good quality forest resources is very small, which directly affects the economic potential and ecological value of the whole forestry industry.…”
Section: Introductionmentioning
confidence: 99%